Synthesis and Characterization of CeO2 samples doped with Bi - Ateş, Tankut; Keser, Serhat; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2024)
In the present paper, the effects of bismuth (Bi) on the structural properties and morphology of cerium dioxide (CeO2) structure. One un-doped and four Bi-doped CeO2 samples were manufactured and characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR), and scanning electron microscopy (SEM) techniques. The XRD and FTIR results confirmed the formation of the CeO2 structure for each sample without any impurity. The crystallinity, average crystallite size and lattice parameter were affected by Bi-content. The amount of the additive of Bi affected the morphology of the as-produced samples.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri